Contrasting responses of bacterial and fungal communities to plant litter diversity in a Mediterranean oak forest. (October 2018) - Santonja, Mathieu; Foucault, Quentin; Rancon, Anaïs; Gauquelin, Thierry; Fernandez, Catherine; Baldy, Virginie; Mirleau, Pascal
Abstract: Tree species diversity of forested ecosystems control the diversity of leaf litter inputs to the soil, with cascading effects on the microbial communities colonizing decomposing litter. However, the extent to which bacterial and fungal communities inhabiting the litter layer are affected by shifts in tree species diversity is not well understood. To investigate the role of litter species diversity, litter species identity and litter functional traits on bacterial and fungal communities of a typical Mediterranean oak forest, we set up a yearly field litterbag experiment that considered leaf litter mixtures of four abundant species: Quercus pubescens, Acer monspessulanum, Cotinus coggygria and Pinus halepensis . We found that both bacterial and fungal communities varied strongly during decomposition but showed distinct succession patterns. Both communities were also strongly influenced by litter species diversity, litter identity and litter functional traits. The intensity and the direction of these effects varied during decomposition. Litter diversity effects were mediated by litter species composition rather than litter species richness, highlighting the importance of litter species identity - and associated litter traits - as drivers of microbial communities. Both the "mass-ratio hypothesis", measured through the community weighted mean (CWM) litter traits, and the "niche complementarity hypothesis", measured through the functional dissimilarity (FD) of litter traits, contributed to litter diversity effects, with a greater relative importance of FD compared to CWM, and with an overall stronger impact on fungal- than on bacterial-communities. Interestingly, increasing FD was related to decreasing bacterial diversity, but increasing fungal diversity. Our findings provide clear evidence that any alteration of plant species diversity produces strong cascading effects on microbial communities inhabiting the litter layer in the studied Mediterranean oak forest. Highlights: Changing plant litter diversity alters microbial diversity and community structure. The intensity and direction of litter diversity effects vary importantly during decomposition. Litter diversity effects are mediated by litter species composition rather than litter species richness. Increasing functional dissimilarity of litter traits decreases bacterial diversity while increases fungal diversity.